DESIGN OF COLLABORATIVE GOVERNANCE MODEL IN HANDLING PLASTIC USE REDUCTION - Wahyudin, Cecep; Oetje Subagdja; Abubakar Iskandar (Jurnal Governansi, 2023)
Reducing the use of plastic is an important issue in handling plastic waste, a national problem as the main pollution element causes air, soil, and water pollution and various environmental and ecosystem damage where human and natural resources develop. The collaborative concept of governance in reducing the use of plastic becomes a government study in a beautiful environment without plastic. The purpose of this research is to design collaborative governance models that can affect the development of plastic use; This research method uses qualitative with a descriptive approach. Informants of this research are government, private/business actors, and the community. The study results showed collaborative governance between the government, the private sector, and the community. However, there still needs to be an increase in collaboration so that it needs to develop in reducing plastic use. The level of collaborative governance concept in reducing the use of plastic in Bogor regency is oriented to a structured process in which there is a constructive involvement of actors with various actions carried out by the government level, private institutions/business actors, and the community in reducing the use of plastic.